Implementation of Qur’an-Based Character Education in Pesantren Disciplinary Policy - Cecep Anwar; Findi Alexsandy; Ilham Nugraha; Sulton Arif (Intiqad: Jurnal Agama dan Pendidikan Islam, 2026)
This study empirically investigates the implementation of Qur’an based character education through disciplinary regulations at Pesantren Al Musyarrofah, Warungkondang, Cianjur. The research adopts a quantitative descriptive survey design. Data were gathered through a five point Likert scale questionnaire distributed to 19 respondents, comprising 11 students and 8 teachers. The analysis employed descriptive statistical techniques, including mean values and categorical assessment. The results indicate that the application of Qur’an based character education through disciplinary policies falls within the good to very good category, particularly with respect to the internalization of Qur’anic values and the substance of the regulations. At the same time, perceptual differences between students and teachers emerged, mainly related to role modeling and the perceived influence of the policies on student behavior.